1993
DOI: 10.1289/ehp.93101s5179
|View full text |Cite
|
Sign up to set email alerts
|

Nonmutagenic carcinogens induce intrachromosomal recombination in dividing yeast cells.

Abstract: A large number of animal and human carcinogens without apparent genotoxic activity exist (nonmutagenic carcinogens)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1994
1994
2010
2010

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Cyclophosphamide is an alkylating agent which can result in guanine adducts in the DNA, mitomycin C is an alkalating cross-linking agent, etoposide is a topoisomerase II inhibitor, and X-radiation causes results in DNA strand breaks and free radicals which can damage DNA. Methylene chloride was chosen for study because it is known to be carcinogenic in animals and causes intrachromosomal recombination but not interchromosomal recombination in yeast (Scheistl, 1993). The induction of inversions in response to all of these agents suggested that chromosomal inversion was a common mutational response to different DNA damaging agents with different mechanisms of genotoxic action.…”
Section: The Pkz1 Assay As An In Vivo Mutation Assaymentioning
confidence: 99%
“…Cyclophosphamide is an alkylating agent which can result in guanine adducts in the DNA, mitomycin C is an alkalating cross-linking agent, etoposide is a topoisomerase II inhibitor, and X-radiation causes results in DNA strand breaks and free radicals which can damage DNA. Methylene chloride was chosen for study because it is known to be carcinogenic in animals and causes intrachromosomal recombination but not interchromosomal recombination in yeast (Scheistl, 1993). The induction of inversions in response to all of these agents suggested that chromosomal inversion was a common mutational response to different DNA damaging agents with different mechanisms of genotoxic action.…”
Section: The Pkz1 Assay As An In Vivo Mutation Assaymentioning
confidence: 99%